Un referendum sull’otto per mille? Riflessioni sulle fonti (Stato, Chiese e pluralismo confessionale, 2013)
l contributo, sottoposto a valutazione, è destinato al n. 2/2013 della Rivista Diritto e religioni, in corso di pubblicazione.SOMMARIO: 1. Introduzione - 2. Il referendum abrogativo e la legge n. 222 del 1985 - 3. L’art. 47 della legge n. 222 del 1985 nel sistema delle fonti … - 4. (segue) … nella “costituzione materiale” e nel diritto internazionale generalmente riconosciuto - 5. La natura “atipica” della legge n. 222 del 1985 - 6.  Il meccanismo dell’otto per mille e il limite delle leggi tributarie ex art. 75 (comma 2) Cost. - 7. L’otto per mille e i principî costituzionali in materia di contribuzione fiscale e spesa pubblica - 8. Brevi note comparative fra otto per mille e cinque per mille - 9. Conclusioni. Il “diritto comune” dell’otto per mille e l’eguale libertà delle confessioni. ABSTRACT:In April 2013 an Italian political party proposed a referendum (as stated in the article 75 of Italian Constitution) to abolish part of the article 47 of the222/1985 Act concerning the public funding to religious denominations with the 0.008 of the income tax (called IRPEF). According to this law all Italian taxpayers can participate to a sort of ‘poll’ to allocate 0.008 of their income tax (IRPEF) to the either the Catholic Church or the State by signing under one of the other in the tax form. The entire fund (i.e. the overall amount of 0,008 of the IRPEF) will then be divided proportionally amongst the choices selected by the tax payer who signed to give 0.008 of their taxes to specific institutions (e.g. the Catholic Church, the State, etc). In doing so, even the tax payers who did not choose any denomination will end up funding one according to the selection made by those who did sign to give their taxes to a religious group or to the State. In this essay the Author analyses some juridical aspects of that particular funding system which represents an important feature of the discipline regulating the relationship between State and Churches, including religious denominations other than Catholicism.